PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LIPAT UNITED - Mulyajati, Rahmanto; Siregar, Salim (STIE Atma Bhakti, 2023)
At this time folding bicycles are still favored by many Indonesian people. Not only as a means of transportation, bicycles have now become a lifestyle for the people of Indonesia. This folding bike is back in trend, several factors are the cause, including maintaining a healthy body, environmental awareness to create clean air in urban areas or just following the prevailing trend, especially due to the Corona Virus (COVID-19) outbreak. The purpose of this study is to determine and analyze the effect of brand image and product quality on the purchasing decision of Folding United bicycles. This research method uses descriptive quantitative method using multiple regression analysis techniques. The results of this study are the results of research on brand image (X1) and product quality (X2) have a simultaneous effect on the variable purchasing decision (Y) United folding bicycle. Purchasing (Y) United Folding Bike. The results of Brand Image (X1) and Product Quality (X2) research have a joint influence of 25.6% on Purchase Decision (Y) United Folding Bike and the remaining 74.4% is influenced by other variables .